Upaya Mencapai Keunggulan Lulusan Melalui Penerapan Manajemen Kurikulum Terpadu di Pesantren Modern Nurul Hakim Tembung-Deli Serdang - Ibrahim Ibrahim; Amini Amini; Akrim Akrim (Journal on Education, 2023)
The purpose of this study is to describe efforts to achieve graduate excellence through the implementation of integrated curriculum management at the Nurul Hakim Tembung-Deli Serdang Modern Islamic Boarding School. This study used a qualitative approach with an analytical descriptive study method. The results of the study show (1) The integrated curriculum planning of the Nurul Hakim Tembung Modern Islamic Boarding School in achieving graduate excellence begins with determining the Vision and Mission, institutional strategy, and institutional output. Determination of the vision and mission, the goals of the institution are prepared based on the deliberations of the leadership of the pesantren with the teachers by prioritizing the concept of graduate excellence. (2) Implementation of integrated curriculum management, namely in the form of curriculum integration with a ratio of 50% Madrasah curriculum and 50% Islamic boarding school curriculum. Implementation of integrated curriculum management consists of intra-curricular, co-curricular and extracurricular. (3) Evaluation of integrated curriculum management, including evaluation of organizational structure, evaluation of Human Resources, and Evaluation of Learning to achieve excellence in graduates. Evaluation is carried out if the output of graduates and the development of students do not have significant results. (4) To achieve the excellence of graduates, the pesantren needs the support of the director of the foundation, the quality of teachers, students, curriculum and learning management. Graduate achievements are provided with religious guidance, foreign language guidance and additional learning for graduates who wish to continue on to Middle Eastern Universities and State Universities.